Effect of Soil Moisture Level and Nutrient Management on Yield, Bio-Chemical Properties and Water Productivity of Black Cumin - Yousuf, MN; Karim, AJMS; Solaiman, ARM; Islam, MS; Zakaria, M (Bangladesh Journal of Agricultural Research, 2023)
A field experiment was conducted at the Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur farm during rabi season of 2017-2018 to evaluate the effects of soil moisture levels and nutrient management on yield, bio-chemical properties and water productivity of black cumin (cv. BARI Kalozira-1) in the Shallow Red-Brown Terrace Soil of Salna series under AEZ-28 (Madhupur Tract). The experiment was set up in a Randomized Complete Block Design (factorial) with three replications comprising 9 treatment combinations having 3 soil moisture levels (Irrigation at 10%, 20% and 30% depletion of soil available water at field capacity) and 3 nutrient management packages: 100% RDF (80-45-50-20-5-2 kg ha-1 of N-P-K-S-Zn-B), 75% RDF + 25% N from cowdung and 50% RDF + 50% N from cowdung. The highest seed yield (1027 kg ha-1), biomass yield (2303 kg ha-1), thymoquinone (3286 mg kg-1 seed), thymol (149 mg kg-1 seed), fixed oil (28.7%), essential oil (0.85%), total consumptive use of water (112 mm) and water productivity (20.5 & 9.14 kg ha-1 mm-1, on the basis of biomass & seed yield, respectively) were obtained from irrigation at 10% depletion of available water along with 75% RDF + 1.98 t ha-1 cowdung. The application of irrigation water at 10% depletion of available water (112.22 mm) with N, P, K, S, Zn and B @ 60, 45, 50, 20, 5 and 2 kg ha-1, respectively + 1.98 t ha-1 cowdung (for supplementing 25% N requirement) appeared to be the best suited treatment package for black cumin cultivation in the study area. Bangladesh J. Agril. Res. 47(3): 309-321, September 2022